Prevalence of thromboembolic events among 8,860 patients with thalassaemia major and intermedia in the Mediterranean area and Iran - Taher, Ali; Isma’eel, Hussain; Mehio, Ghassan; Bignamini, Daniela; Kattamis, Antonis; Rachmilewitz, Eliezer A.; Cappellini, Maria Domenica (Thrombosis and Haemostasis, 2006)
Beta-thalassaemia isa congenital haemolytic anaemia characterized by partial (intermedia, TI) or complete (major, TM) deficiency in the production of β-globin chains.The primary aim of this study was to determine the prevalence of thromboembolic events in patients with β-thalassaemia.To achieve this,a multiple-choice questionnaire was sent to 56 tertiary referral centres in eight countries (Lebanon, Italy, Israel, Greece, Egypt, Jordan, Saudi Arabia and Iran), requesting specific information on patients who had experienced a thromboembolic event.The study demonstrated that thromboembolic events occurred ina clinically relevant proportion (1.65%) of 8,860 thalassaemia patients (TI – 24.7% or TM – 75.3%) from the Mediterranean and Iran. Thromboembolism occurred 4.38 times more frequently in TI thanTM (p<0.001), with more venous events occurring inTI and more arterial events occurring in TM.Thrombosis in thalassaemia was also more common in females, splenectomized patients and those with profound anaemia (haemoglobin <9 g/dl). Due to the increased risk of thromboembolic events, the rationale for splenectomy should perhaps be re-assessed and the role of transfusion therapy for the prophylaxis of thrombosis, among other complications, be evaluated prospectively.
Keywords: Thrombosis; thalassaemia intermedia; thalassaemia major